(untitled) (Journal of Economic Research & Business Administration, 2019)
Measuring competitiveness in central Asian post-socialist countries is problematic as many well-known metrics systems fail to warn about bankruptcy risks sufficiently early or at all. This article aims to present options for analyzing bankruptcy and creditworthiness models developed and used frequently in the Czech Republic. Bankruptcy likelihood is frequently measured by two famous models, the Altman z-score model, and Taffler z-score model. But there are other models which can be considered as more useful for companies in Kazakhstan such as IN99, IN01, IN05, and a creditworthiness model. The IN models were developed in an environment of Czech economy developing from socialistic to market oriented during the 1990s. During this period the IN models were developed so they are newer than the other two more famous models mentioned. Since the Czech Republic uses IFRS accounting standard which is also frequently used in Kazakhstan that is another reason why the IN models should be considered for wider use by companies in Kazakhstan.